ANALISIS PEMETAAN DAERAH RAWAN BANJIR DI KOTA MEDAN TAHUN 2020 - Nabila Anggraini; Booby Pangaribuan; Asri Patria Siregar; Ghannes Sintampalam; Amri Muhammad; M Ridha Syafii Damanik; M Taufik Rahmadi (Geography Education Study Program, Universitas Samudra, 2021)
Medan City is one of the areas included in the flood-prone category in North Sumatra. This natural disaster always occurs every year when the rainy season enters. The purpose of this research is to map the level of flood hazard in Medan City. The type of method used in this study is a qualitative method by looking at the effect of each flood parameter to identify the level of flood vulnerability in Medan City. The parameters used are the slope of the slope, soil type, and rainfall which will then be processed using the overlay method to obtain the flood hazard class in Medan City. The results showed that the distribution of flood-prone areas in Medan City was in all parts of the area which were categorized into four levels of vulnerability, namely very low with an area of ​​248 hectares, low with an area of ​​1,817 hectares, medium with an area of ​​11,465 hectares, and high categories with an area of ​​14,037 hectares.